African horse sickness in The Gambia: circulation of a live-attenuated vaccine-derived strain - (:unkn) unknown (My University, 2011)
African horse sickness virus serotype 9 (AHSV-9) has been known for some time to be circulating amongst equids in West Africa without causing any clinical disease in indigenous horse populations. Whether this is due to local breeds of horses being resistant to disease or whether theAHSV-9 strains circulating are avirulent is currently unknown. This study shows that the majority (96%) of horses and donkeys sampled across The Gambia were seropositive for AHS, despite most being unvaccinated and having no previous history of showing clinical signs of AHS. Most young horses (<3 years) were seropositive with neutralizing antibodies specific to AHSV-9. Eight young equids (<3 years) were positive for AHSV-9 by serotype-specific RT–PCR and live AHSV-9 was isolated from two of these horses. Sequence analysis revealed the presence of an AHSV-9 strain showing 100% identity to Seg-2 of the AHSV-9 reference strain, indicating that the virus circulating in The Gambia was highly likely to have been derived from alive-attenuated AHSV-9 vaccine strain.
Keywords: African Research